The body move: revising portuguese female poetry of the first quarter of the twentieth century - Pinto, Isabel (2016)
The first quarter of the twentieth century in Portugal was characterised by a series of important historical and political events: the Regicide (1st February 1908), the fall of the Monarchy and establishment of the Republic (5th October 1910), and the First World War (1914-1918). By this time, women could not yet vote and they were systematically ignored in the debate of crucial social issues. Therefore, the main question here addressed is how poetry as free embodiment can take part in a gender revolution, promoting the feminist turn. The answer lies in the consequent breakout of female sentimental literature, which entitled women to reveal themselves, by enabling the poetic scrutiny of their intimacy through a particular focus on the body as prime referent. In this way, they dared to expose dreams, desires, fulfilments and despairs, firming an identity pact through poetry, and engendering a collective voice with social meaning. The published poems here analysed convey the idea that being a woman was something valuable and unique, and, at the same time, manage to inscribe female poets such as Virgínia Vitorino and Zulmira Falcarreira in the Portuguese intellectual mainstream.